Incidencia de los medios de comunicación, redes sociales y fake news durante las manifestaciones sociales de octubre 2019 en Ecuador - Larrea Ayala, Ana; Avellaneda Galarza, Joely; Chamorro Loyo, Antonella; Guerrero Pasquel, Milena; Mestanza Yépez, Emily; Cadena, Andy Steve (Revista Ecos de la Academia, 2023)
The national strike of October 2019 in Ecuador showed a scenario of social unrest, violence, protests, clashes between rioters, carriers and the indigenous movement against the government’s decision to eliminate gasoline subsidies. In this article, information, data, news and interviews published by the media such as Teleamazonas, a private traditional mass media, and Wambra, a community digital media, were compiled with the aim of make an exhaustive analysis of the communication diffused and the role played by the media during the 11 days of protest. Through the research techniques of news content analysis, in addition to interviews with specialists in journalism and digital communication, it was possible to determine that most of the hypotheses were true because they were focus on highlighting the diffusion of biased and unobjective news from both media, because to a large extent or to a low degree they assumed a biased position regarding the event. In addition to the quantitative and qualitative analysis of the type of sources used, scope, level of objectivity and persuasion. Also, a brief inquiry was made about the influence of social networks and the spread of fake news in the collective thought of society.